2018
DOI: 10.1371/journal.pone.0208999
|View full text |Cite
|
Sign up to set email alerts
|

Covariation of the endocranium and splanchnocranium during great ape ontogeny

Abstract: That great ape endocranial shape development persists into adolescence indicates that the splanchnocranium succeeds brain growth in driving endocranial development. However, the extent of this splanchnocranial influence is unknown. We applied two-block partial least squares analyses of Procrustes shape variables on an ontogenetic series of great ape crania to explore the covariation of the endocranium (the internal braincase) and splanchnocranium (face, or viscerocranium). We hypothesized that a transition bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 96 publications
0
8
1
Order By: Relevance
“…However, the results in the present study only partially corresponded to these previous studies, as the magnitude of integration in the chondrocranium/face complex was significantly higher than for the skull as a whole in juvenile groups (p < .001), but not in adults (U = 500,530, p = .9675; Table S1). One possible reason for the discrepancy between the present and previous investigations is that some studies were performed on endocranial morphology of the basicranium/face complex (Gkantidis & Halazonetis, 2011;Lieberman, Pearson, et al, 2000;Lieberman, Ross, et al, 2000;Neaux, 2017;Neaux et al, 2018;Neaux, Guy, Gilissen, Coudyzer, & Ducrocq, 2013;Neaux, Wroe, Ledogar, Heins Ledogar, & Sansalone, 2019;Scott et al, 2018). Nevertheless, our results likely indicate that the chondrocranium/face complex is not as tightly integrated in adults as it is in juveniles.…”
Section: Chondrocranium/face Complexcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the results in the present study only partially corresponded to these previous studies, as the magnitude of integration in the chondrocranium/face complex was significantly higher than for the skull as a whole in juvenile groups (p < .001), but not in adults (U = 500,530, p = .9675; Table S1). One possible reason for the discrepancy between the present and previous investigations is that some studies were performed on endocranial morphology of the basicranium/face complex (Gkantidis & Halazonetis, 2011;Lieberman, Pearson, et al, 2000;Lieberman, Ross, et al, 2000;Neaux, 2017;Neaux et al, 2018;Neaux, Guy, Gilissen, Coudyzer, & Ducrocq, 2013;Neaux, Wroe, Ledogar, Heins Ledogar, & Sansalone, 2019;Scott et al, 2018). Nevertheless, our results likely indicate that the chondrocranium/face complex is not as tightly integrated in adults as it is in juveniles.…”
Section: Chondrocranium/face Complexcontrasting
confidence: 99%
“…Previous investigations have reported high magnitudes of integration between the basicranium and face throughout ontogeny in humans (Gkantidis & Halazonetis, 2011) and other great apes (Scott, Strauss, Hublin, Gunz, & Neubauer, 2018). Moreover, these previous studies also reported that degrees of integration between the basicranium and face increased throughout ontogeny (Gkantidis & Halazonetis, 2011;Scott et al, 2018). However, the results in the present study only partially corresponded to these previous studies, as the magnitude of integration in the chondrocranium/face complex was significantly higher than for the skull as a whole in juvenile groups (p < .001), but not in adults (U = 500,530, p = .9675; Table S1).…”
Section: Chondrocranium/face Complexmentioning
confidence: 91%
“…The vast majority of the research on patterns of integration and covariation in hominoids are focused on the skull (e.g., Ackermann, 2002; Bastir, 2008; Bastir et al, 2005; Bookstein et al, 2003; Bruner, Pereira‐Pedro, & Bastir, 2017; Mitteroecker & Bookstein, 2008; Neaux et al, 2018; Profico et al, 2017; Püschel, Friess, & Manríquez, 2020; Scott et al, 2018; Singh, Harvati, Hublin, & Klingenberg, 2012; Stelzer, Gunz, Neubauer, & Spoor, 2018), but studies investigating integration and covariation within and between elements of the torso are scarce (Arlegi et al, 2020; Grabowski et al, 2011; Huseynov et al, 2017; Lewton, 2012; Middleton, 2015; Torres‐Tamayo et al, 2018; C. V. Ward et al, 2015). Among those, Middleton (2015) quantified and compared for the first time trunk relationships between H. sapiens and Pan collecting linear metrics and 3D coordinates on disarticulated trunk skeletal elements.…”
Section: Discussionmentioning
confidence: 99%
“…Two‐block Partial Least Squares (2B‐PLS) analysis has been revealed as a useful method to statistically assess the covariation between two different sets of original variables, for example, between two sets of shape data (2D or 3D) (Adams & Collyer, 2016; Arlegi et al, 2018; Bastir, Rosas, & Sheets, 2005; Bookstein et al, 2003; Klingenberg & Marugán‐Lobón, 2013; Mitteroecker & Bookstein, 2007; Mitteroecker, Gunz, Neubauer, & Müller, 2012; Neaux et al, 2018; Rohlf & Corti, 2000; Scott, Strauss, Hublin, Gunz, & Neubauer, 2018; Torres‐Tamayo et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation